2012
DOI: 10.1001/jama.2012.9071
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Exposure-Based Therapy for Co-occurring Posttraumatic Stress Disorder and Substance Dependence

Abstract: Context There is concern that exposure therapy, an evidence-based cognitivebehavioral treatment for posttraumatic stress disorder (PTSD), may be inappropriate because of risk of relapse for patients with co-occurring substance dependence.Objective To determine whether an integrated treatment for PTSD and substance dependence, Concurrent Treatment of PTSD and Substance Use Disorders Using Prolonged Exposure (COPE), can achieve greater reductions in PTSD and substance dependence symptom severity compared with us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
293
3
1

Year Published

2012
2012
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 282 publications
(320 citation statements)
references
References 34 publications
23
293
3
1
Order By: Relevance
“…Mills et al [12] in Sydney, Australia, attempted to determine whether an integrated treatment for PTSD and substance dependence, concurrent treatment of PTSD and substance use disorders using prolonged exposure (COPE), can achieve greater reduction in PTSD and substance dependence symptom severity than the usual treatment for substance dependence. Participants were randomly assigned to COPE (n = 55; 13 individual 90-min sessions) plus usual treatment, or usual treatment alone (n = 48; any type of substance abuse treatment, including outpatient counseling, inpatient or outpatient detoxification, residential rehabilitation, and pharmacotherapies such as methadone, buprenorphine, naltrexone etc.).…”
Section: Management Of Posttraumatic Stress Disordermentioning
confidence: 99%
“…Mills et al [12] in Sydney, Australia, attempted to determine whether an integrated treatment for PTSD and substance dependence, concurrent treatment of PTSD and substance use disorders using prolonged exposure (COPE), can achieve greater reduction in PTSD and substance dependence symptom severity than the usual treatment for substance dependence. Participants were randomly assigned to COPE (n = 55; 13 individual 90-min sessions) plus usual treatment, or usual treatment alone (n = 48; any type of substance abuse treatment, including outpatient counseling, inpatient or outpatient detoxification, residential rehabilitation, and pharmacotherapies such as methadone, buprenorphine, naltrexone etc.).…”
Section: Management Of Posttraumatic Stress Disordermentioning
confidence: 99%
“…There were no data on how concurrent psychotherapies may have affected outcomes or whether the couples were compensated financially for their participation in the trial, and neither the patients assigned to the wait-list condition nor patients who dropped out of treatment were included in the follow-up assessment. From a clinical perspective, the study sample also appeared generally "easier to treat" than is typical in community settings (including the study by Mills et al 3 ), as indicated by baseline measurements of relationship satisfaction, a general lack of severe comorbidities, and the support of an intimate partner who was willing to participate in treatment. In the report by Monson et al, 4 the sample was predominantly white and employed, with virtually no substance use disorder at baseline.…”
mentioning
confidence: 99%
“…2 In this issue of JAMA, the findings of 2 randomized controlled trials of interventions for PTSD expand the boundaries of treatment to relatively underserved populations: the trial by Mills et al 3 assesses interventions in persons with PTSD and substance dependence, and the trial by Monson et al 4 assesses interventions in couples in which 1 partner has PTSD. 4 The trial by Mills et al 3 evaluated Concurrent Treatment of PTSD and Substance Use Disorders Using Prolonged Exposure (COPE) plus usual treatment for substance dependence (n = 55) vs usual treatment for substance dependence alone (n=48). COPE involved an individual modality treatment totaling 19.5 hours, whereas usual treatment was any type of substance use treatment available in the patient's community, including counseling, detoxification, residential rehabilitation, and pharmacotherapy.…”
mentioning
confidence: 99%
“…[6][7][8][9][10][11] This issue of JAMA includes reports of 3 new randomized trials of interventions: a trial of screening for intimate partner violence 12 and 2 trials of interventions for posttraumatic stress disorder for survivors of violence. 13,14 The implications of these trial reports for clinical practice and public health are discussed in accompanying Editorials, 15,16 as are the methodologic strengths and limitations of these studies. In this context, it is worth reflecting on what researchers, public health and international aid workers, and clinicians have been able to accomplish in the past several years of intensive work in the fields of violence and human rights.…”
mentioning
confidence: 99%